Kampanye dalam Pemasaran Politik dan Brand Politik - Winda Kustiawan; Nazmi Wiki Kartika; Cindy Indarti Kesuma; Farid Arkana Silalahi; Abdul Majid Nasution (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
Campaign in political marketing is a series of activities that have been planed, strategic and tactical in spreading a political meaning in the voters to make the candidate to be nominated a success. Political brand itself includes the 4p, namely product, promotion, price and placement. This paper examines how the development of campaigns in political marketing and how the emergence of advertising or what is called a political brand. By using descriptive qualitative analiysis, researches want to analyze the data by describing or describing the data collected properly related to compaigns in political marketing and political brands. The result of this study find that campaigns in political marketing can have positive and negative impacts on the election of candidates or candidacy related to politics and how this political brand is also beneficial for the owner of the advertisement who wants to be promoted.